Instant Optimizing Embedded Systems Using Busybox - Zhangjin, Wu; Ziqiang, Cao (Packt Publishing, Limited, 2013)
Filled with practical, step-by-step instructions and clear explanations for the most important and useful tasks. A step-by-step guide which provides concise and clear recipes for getting started with Busybox.If you are an embedded system developer or Android developer who wishes to learn to build an embedded (Android Linux) system from scratch, as well as to optimize the system performance, then this book will be great for you. Its assumed that you have some experience in Linux and UNIX utilities. If you are a new developer, this book will also help you to get started with Busybox and Android Linux development.